Transfer of ritual - Langer, Robert; Lüddeckens, Dorothea; Radde-Antweiler, Kerstin; Snoek, Joannes A. M. (Journal of ritual studies, 2006)
This paper investigates an aspect of the dynamics of ritual which is so far unresearched and hardly systematized: the phenomenon of 'transfer of ritual'. It attempts to bring order to the issues associated with this thorny problem, dividing them into two independent 'sets' (together also referred to as a 'matrix'), which can, in our opinion, be used as an analytical instrument. During the last three years, the possibilities for application of this instrument were tested and further enhanced.
Gesehen am 23.02.2021
Keywords: Rezeption; Ritual; Ritus